Method for preparing ceramic fiber paper composite nano aerogel
By pretreating ceramic fiber paper and building a transition layer, combining solvent replacement and surface modification, an efficient drying method is used to solve the problems of uniform composite and thermal insulation performance of ceramic fiber paper and aerogel composite materials, and a high-performance, green and environmentally friendly composite aerogel material preparation is achieved.
Patent Information
- Application Number
- CN202510016585.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-04
AI Technical Summary
The existing methods of combining ceramic fiber paper with aerogel to prepare high-performance materials are difficult to achieve uniform composite, resulting in the overall performance of the material being affected, and the traditional drying process will lead to collapse of the aerogel structure and reduce thermal insulation performance.
By pretreating ceramic fiber paper, specific functional groups are introduced to enhance chemical bonding with aerogel precursors, and a transition layer is constructed to promote aerogel growth, combined with solvent replacement and surface modification, solvent removal is carried out by supercritical drying or freeze-drying.
It significantly improves the interface bonding strength between ceramic fiber paper and aerogel, optimizes the microstructure of the material, improves the flexibility and thermal insulation properties of the material, reduces thermal conductivity, expands the application range of the material, and at the same time realizes a green and environmentally friendly preparation process.
Smart Images

Figure CN119751015A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical material processing, and in particular relates to a method for preparing ceramic fiber paper composite nano aerogel. Background Art
[0002] With the rapid development of modern industry, the demand for high-performance thermal insulation, heat preservation, fire protection and other multifunctional materials is growing. As a traditional thermal insulation material, ceramic fiber paper has certain high temperature resistance and thermal insulation properties, and its fiber structure gives it relatively good flexibility and processability. Aerogel is a material with extremely low density, high porosity and excellent thermal insulation properties, showing great potential in the field of thermal insulation.
[0003] Existing methods for preparing high-performance materials by compounding ceramic fiber paper with aerogel have many shortcomings and application limitations. In terms of preparation methods, traditional composite processes often make it difficult to achieve uniform composites of ceramic fiber paper and aerogel. For example, in the impregnation method, due to improper viscosity control of the aerogel precursor solution or unreasonable impregnation conditions, the aerogel is easily unevenly distributed on the ceramic fiber paper, some areas are over-impregnated to form agglomerates, and some areas are under-impregnated, thereby affecting the overall performance of the material. Moreover, traditional drying processes, such as normal pressure drying or ordinary vacuum drying, will cause the aerogel structure to collapse during the removal of the solvent due to the capillary force inside the aerogel, resulting in a decrease in porosity and thermal insulation performance, which in turn causes the composite material to be unable to give full play to the respective advantages of ceramic fiber paper and aerogel. In terms of application, due to the defects of the above-mentioned preparation methods, the application scope of the resulting composite material is greatly limited. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a method for preparing ceramic fiber paper composite nano aerogel which is green and environmentally friendly, and the processed product has good flexibility and thermal insulation and high bonding degree.
[0005] The present invention is achieved through the following technical solutions: A method for preparing ceramic fiber paper composite nano aerogel comprises the following steps: A. Ceramic fiber paper pretreatment: soak the ceramic fiber paper in a solution containing an organic silane coupling agent and then dry it; B. Preparation of transition layer: Select nanoparticles and evenly disperse them in the aerogel precursor solution, then coat the mixture on the ceramic fiber paper dried in step A, and then preliminarily cure it; C. Aerogel growth: placing the ceramic fiber paper coated with the transition layer in step B into a reaction vessel, injecting the remaining aerogel precursor solution to immerse the ceramic fiber paper, adding a catalyst to adjust the pH value of the solution, performing a gelation reaction, and aging in an aging solution after the reaction is completed; D. Solvent replacement and surface modification: After the aerogel growth in step C is completed, the aerogel is first placed in a replacement solvent for solvent replacement; then the composite aerogel after solvent replacement is immersed in a solution containing an organosilicon modifier for surface modification; E. Drying treatment: Finally, the composite aerogel in step D is subjected to supercritical drying or freeze drying to remove the solvent to obtain a ceramic fiber paper composite aerogel material.
[0006] The molecular structure of the organosilane coupling agent in step A comprises a functional group that reacts with the hydroxyl group on the surface of the ceramic fiber and a group that interacts with the aerogel precursor.
[0007] The aerogel precursor in step B is a silica sol formed by mixing tetraethyl orthosilicate, ethanol, and deionized water and adding hydrochloric acid as a catalyst; in the aerogel precursor, the molar ratio of tetraethyl orthosilicate, ethanol, and deionized water is 1:(3-5):(4-6), the concentration of hydrochloric acid is 0.1-0.3 mol / L, the stirring reaction temperature is 50-60°C, and the stirring reaction time is 3-5 hours.
[0008] In step A, the organic silane coupling agent is γ-aminopropyltriethoxysilane; the concentration of the organic silane coupling agent solution is 3%-8%, the soaking time is 2-4 hours, the temperature is controlled at 35-45°C, the drying temperature is 55-65°C, and the drying time is 1.5-2.5 hours.
[0009] In step B, the nanoparticles are nano-silicon dioxide particles or nano-titanium dioxide particles; the particle size of the nanoparticles is 15-25 nm, the mass ratio of the nanoparticles to the aerogel precursor is 1:4-1:6, the coating thickness is 8-12 μm, the initial curing temperature is 45-55° C., and the initial curing time is 25-35 minutes.
[0010] In the step C, the catalyst is ammonia water, ammonia water is added to adjust the solution pH to 7-9, the gelation reaction temperature is 55-65° C., the gelation reaction time is 3-5 hours, and the aging time is 10-14 hours.
[0011] In the step D, the replacement solvent is an organic solvent with a low boiling point and miscible with the solvents in steps A to E, the immersion temperature is 50-60°C, and the immersion time is 10-20 hours; the organosilicon modifier is methyltriethoxysilane or hexamethyldisilazane; the concentration of the organosilicon modifier is 2%-5%, the immersion temperature is 50-60°C, and the immersion time is 6-10 hours.
[0012] The displacement solvent is acetone.
[0013] In step E, the medium used for supercritical drying is CO2, the temperature is 50-70°C, the pressure is 8-12 MPa, and the drying time is 5-8 hours; the temperature of freeze drying is -35 to -45°C, the vacuum degree is 40-60Pa, and the drying time is 15-25 hours.
[0014] Beneficial effects of the present invention: 1) The present invention performs special surface treatment on the ceramic fiber paper before compounding, and enhances the chemical bonding between the ceramic fiber paper and the aerogel precursor by introducing specific functional groups, so that the two are more closely combined, and the interfacial bonding strength between the ceramic fiber paper and the aerogel is significantly improved, thereby greatly improving the overall mechanical properties of the composite aerogel material.
[0015] 2) Construct a unique layered composite structure, optimize the microstructure of the material and further enhance the flexibility and thermal insulation performance of the material by leveraging the stress dispersion effect of nanoparticles in the transition layer and their promotion of aerogel growth.
[0016] 3) Through the synergistic effect of solvent replacement and surface modification, solvent replacement is used to effectively remove impurities and organic solvents remaining inside the ceramic fiber paper wet gel, thereby improving the purity and uniformity of the material; at the same time, surface modification is carried out at a specific stage to further optimize the interface compatibility between ceramic fiber paper and aerogel and enhance the composite effect.
[0017] 4) Reduce the thermal conductivity of materials, improve thermal insulation performance, reduce heat transfer, achieve more efficient energy saving in industrial insulation and other fields, and reduce production costs and energy consumption.
[0018] 5) Adopt green and environmentally friendly preparation technology to reduce the negative impact on the environment by recycling and reusing solvents and reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention is further described in detail below with reference to the accompanying drawings.
[0020] Figure 1 It is a reaction principle diagram of the present invention.
[0021] Figure 2It is a schematic diagram of the preparation process of the present invention.
[0022] Figure 3 Schematic diagram of the burn-through experiment of the present invention DETAILED DESCRIPTION
[0023] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0024] It should be noted that the structures, proportions, sizes, etc. drawn in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportional relationship or adjustment of the size should still fall within the scope of the technical content disclosed by the present invention without affecting the effects and purposes that can be achieved by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and so on quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical content.
[0025] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. It should be noted that the terms "include", "comprise" or any other variants are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. Example 1
[0026] 1) Select ceramic fiber paper and soak it in a 5% γ-aminopropyltriethoxysilane solution for 3 hours at a temperature of 40°C. After soaking, take it out and dry it at 60°C for 2 hours.
[0027] 2) Prepare the transition layer, take nano-silicon dioxide particles with a particle size of 20nm, mix them with the silica sol precursor at a mass ratio of 1:5, and evenly coat the mixture on the ceramic fiber paper with a coating thickness of 10μm. After coating, initially cure at 50°C for 30 minutes. The silica sol precursor is prepared by mixing ethyl orthosilicate with ethanol and deionized water at a molar ratio of 1:4:5, adding hydrochloric acid with a concentration of 0.2mol / L, and stirring at 50°C for 5 hours.
[0028] 3) Place the ceramic fiber paper coated with the transition layer into the reaction vessel, inject the remaining silica sol precursor solution, add ammonia water to adjust the pH value to 8, and perform gelation reaction at 60°C for 4 hours. After the reaction is completed, age it in an aging solution of the same system with a concentration half that of the original solution for 12 hours.
[0029] 4) The composite wet gel was placed in acetone and replaced at 55°C for 15 hours; then, it was immersed in an ethanol solution containing 3% methyltriethoxysilane and modified at 60°C for 6 hours.
[0030] 5) Finally, the composite wet gel was dried using supercritical carbon dioxide at a temperature of 60°C and a pressure of 10 MPa for 6 hours to obtain a high-performance ceramic fiber paper composite aerogel material. Example 2
[0031] 1) Ceramic fiber paper was soaked in 8% γ-aminopropyltriethoxysilane solution for 2 hours at 35°C, and then dried at 55°C for 2.5 hours.
[0032] 2) The transition layer is made of nano-titanium dioxide particles with a particle size of 15nm and a silica sol precursor in a mass ratio of 1:3, with a coating thickness of 8μm. After coating, the coating is initially cured at 45°C for 40 minutes. The silica sol precursor is prepared by mixing ethyl orthosilicate with ethanol and deionized water in a molar ratio of 1:3:4, adding hydrochloric acid with a concentration of 0.1mol / L, and stirring the reaction at 55°C for 4 hours.
[0033] 3) Place the ceramic fiber paper coated with the transition layer into the reaction vessel, inject the remaining silica sol precursor solution, add ammonia water to adjust the pH value to 9, and perform gelation reaction at 55°C for 5 hours. After the reaction is completed, age it in an aging solution of the same system with a concentration half that of the original solution for 15 hours.
[0034] 4) The composite wet gel was placed in acetone and replaced at 60°C for 20 hours; then, it was immersed in an ethanol solution containing 2% hexamethyldisilazane and modified at 55°C for 8 hours.
[0035] 5) The modified composite wet gel was freeze-dried, first frozen at -40°C, and then dried at a vacuum degree of 50 Pa for 20 hours to obtain a high-performance composite aerogel material.
[0036] Comparative Example 1 1) Directly immerse the ceramic fiber paper in a silica sol precursor solution that has not been specially treated for 5 hours. The silica sol precursor is prepared by mixing ethyl orthosilicate with ethanol and deionized water in a molar ratio of 1:5:6, adding 0.3 mol / L hydrochloric acid, and stirring at 55°C for 2 hours.
[0037] 2) Place the dried sample in a reaction vessel, add ammonia water to adjust the pH value to 8, and perform gelation reaction at 60°C for 6 hours. After the gelation reaction is completed, age it in an aging solution of the same system with a concentration half that of the original solution for 18 hours. Finally, supercritical carbon dioxide drying is used to obtain a traditional composite aerogel material at a temperature of 55°C, a pressure of 10MPa, and a drying time of 5 hours.
[0038] Comparative Example 2 (conventional preparation method) 1) A silica sol precursor was prepared by mixing ethyl orthosilicate with ethanol and deionized water in a molar ratio of 1:4:4, adding 0.2 mol / L hydrochloric acid, and stirring the mixture at 50° C. for 3 hours.
[0039] 2) Select ceramic fiber paper, put it into a reaction container, adjust the pH to 9 by adding ammonia water to the silica sol precursor solution, immerse it on the ceramic fiber paper, and perform gelation reaction at 50° C. for 4 hours.
[0040] 3) The wet gel of ceramic fiber paper was immersed in an ethanol solution and replaced at 55°C for 16 hours; then immersed in an ethanol solution containing 2% hexamethyldisilazane and modified at 55°C for 6 hours.
[0041] 4) The modified ceramic fiber paper wet gel was subjected to supercritical drying, using carbon dioxide as the medium, and dried for 6 hours at a temperature of 55° C. and a pressure of 8 MPa to obtain a conventional ceramic fiber paper composite aerogel material.
[0042] The performance of the composite aerogel materials prepared in the above examples and comparative examples was tested, and the results are shown in the following table:
[0043] Performance tests were performed on the high-performance ceramic fiber paper composite aerogel materials prepared in Example 1 and Example 2 and the composite aerogel materials in Comparative Example 1 and Comparative Example 2. The results show that the high-performance composite aerogel materials prepared by the present invention have a tensile strength improved by 30%-40% and a bending strength improved by 20%-30% in terms of mechanical properties compared with similar materials prepared by conventional methods; in terms of thermal insulation performance, the thermal conductivity is reduced by 25%-35%.
[0044] Figure 3 This is a burn-through experiment diagram of the present invention. A sample with a thickness of 3.0 mm of the present invention was subjected to a 1200°C flame spray gun for 30 minutes. The experiment proves that the sample of the present invention cannot be burnt through. The sample prepared by the present invention has good oxidation resistance, can remain stable at high temperatures, and has low mass loss rate and shrinkage rate.
[0045] The protection scope of the present invention is not limited to the technical solutions disclosed in the specific implementation methods. Any modifications, equivalent replacements, improvements, etc. made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing ceramic fiber paper composite nano aerogel, characterized in that The following steps are involved: A. Ceramic fiber paper pretreatment: soak the ceramic fiber paper in a solution containing an organic silane coupling agent and then dry it; B. Preparation of transition layer: Select nanoparticles and evenly disperse them in the aerogel precursor solution, then coat the mixture on the ceramic fiber paper dried in step A, and then preliminarily cure it; C. Aerogel growth: placing the ceramic fiber paper coated with the transition layer in step B into a reaction vessel, injecting the remaining aerogel precursor solution to immerse the ceramic fiber paper, adding a catalyst to adjust the pH value of the solution, performing a gelation reaction, and aging in an aging solution after the reaction is completed; D. Solvent replacement and surface modification: After the aerogel growth in step C is completed, the aerogel is first placed in a replacement solvent for solvent replacement; then the composite aerogel after solvent replacement is immersed in a solution containing an organosilicon modifier for surface modification; E. Drying treatment: Finally, the composite aerogel in step D is subjected to supercritical drying or freeze drying to remove the solvent to obtain a ceramic fiber paper composite aerogel material.
2. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 1, characterized in that: The molecular structure of the organosilane coupling agent in step A comprises a functional group that reacts with the hydroxyl group on the surface of the ceramic fiber and a group that interacts with the aerogel precursor.
3. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 1, characterized in that: The aerogel precursor in step B is a silica sol formed by mixing tetraethyl orthosilicate, ethanol, and deionized water and adding hydrochloric acid as a catalyst; in the aerogel precursor, the molar ratio of tetraethyl orthosilicate, ethanol, and deionized water is 1:(3-5):(4-6), the concentration of hydrochloric acid is 0.1-0.3 mol / L, the stirring reaction temperature is 50-60°C, and the stirring reaction time is 3-5 hours.
4. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 1, characterized in that: In step A, the organic silane coupling agent is γ-aminopropyltriethoxysilane; the concentration of the organic silane coupling agent solution is 3%-8%, the soaking time is 2-4 hours, the temperature is controlled at 35-45°C, the drying temperature is 55-65°C, and the drying time is 1.5-2.5 hours.
5. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 1, characterized in that: In step B, the nanoparticles are nano-silicon dioxide particles or nano-titanium dioxide particles; the particle size of the nanoparticles is 15-25 nm, the mass ratio of the nanoparticles to the aerogel precursor is 1:4-1:6, the coating thickness is 8-12 μm, the initial curing temperature is 45-55° C., and the initial curing time is 25-35 minutes.
6. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 1, characterized in that: In the step C, the catalyst is ammonia water, ammonia water is added to adjust the solution pH to 7-9, the gelation reaction temperature is 55-65° C., the gelation reaction time is 3-5 hours, and the aging time is 10-14 hours.
7. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 1, characterized in that: In the step D, the replacement solvent is an organic solvent with a low boiling point and miscible with the solvents in steps A to E, the immersion temperature is 50-60°C, and the immersion time is 10-20 hours; the organosilicon modifier is methyltriethoxysilane or hexamethyldisilazane; the concentration of the organosilicon modifier is 2%-5%, the immersion temperature is 50-60°C, and the immersion time is 6-10 hours.
8. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 8, characterized in that: The displacement solvent is acetone.
9. The method for preparing ceramic fiber paper composite nano-aerogel according to claim 1, characterized in that: In step E, the medium used for supercritical drying is CO2, the temperature is 50-70°C, the pressure is 8-12 MPa, and the drying time is 5-8 hours; the temperature of freeze drying is -35 to -45°C, the vacuum degree is 40-60Pa, and the drying time is 15-25 hours.